Flutter Analysis of High Aspect Ratio Wing of Sailplane Aircraft - Khoirun Nisa, Anis; A.Ndaomanu, Yorgi; A. Sasongko, R.; Gunawan, L; Mulyanto, T.; Jusuf, Annisa (International Journal of Engineering and Technology, 2018)
Sailplane aircraft that has high aspect ratio wing are often used in sports competitions in the sports gliding branch. One of the biggest aeroelastic problem of a plane with high aspect ratio wing is flutter. The occurence of flutter are caused by the combination of two or more normal modes. Flutter phenomenon that occurs in the sailplane aircraft generally are caused by the movement of aileron. To meet the certification purposes, flutter speed of aircraft should not occur within the safe limit of flight envelope. Certification that is used as a reference of design process is arranged by EASA at CS 22 that explain about the certification of sailplane aircraft. Flutter analysis was done using MSC NASTRAN/ PATRAN/ FLDS software. Analysis of the structure and aerodynamics plate is done by using the finite element method approach. The unsteady aerodynamic analysis was done using the Doublet-Lattice method, then flutter analysis was done using the PKNL method. Mode participation factor method is used to know the minimum mode shape that will appear when flutter occurs. Flutter speed is proportional to the magnitude of the wing stuctural stiffness. Beside that, aileron rod stiffness also give effects on flutter phenomenon. In this preliminary study, flutter analysis was done by varying aileron rod stiffness and general wing stiffness. Using the flutter analysis result, it can be seen that the differences on magnitude of aileron rod stiffness and general wing stiffness will have effect on the flutter speed magnitude.Â Â